Library and social networking: a new tool in information management (2009)
The paper discusses social networking as a new tool in information management, using Facebook as case study. It explicates how social Networking can enhance library outreach and librarians’ collaboration. It presents social networking as new tool in information management that is capable of creating futures -prospects, opportunities, hope for library users and information and library professionals. For the purpose of this work three groups were created on Facebook. One for library users and two for Librarians. Social networking sites could be effectively used to disseminate information and promote pleasant professional relationship among librarians and library users. It encourages academic collaboration. With Facebook group, pictures of memorable events could be shared, news could be posted, and meeting, conference and workshop could be announced.